PEREMPUAN PENYAPU JALAN DI KOTA PEKANBARU (Studi Tentang Perempuan Sebagai Orangtua Tunggal Dalam Keluarga) - Darmawan Efendi; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was carried out in Pekanbaru City, Riau Province. The purpose of this study was to determine the time division of street sweeper women as single parents in the family, in activities in the family and work in the city of Pekanbaru. The topic of focus of this research is role conflict that occurs in the family and women's work of street sweepers in Pekanbaru City. Sampling techniques are accidental sampling and determine the number of samples as many as 7 people. The author uses qualitative methods and data instruments are observation, interviews and documentation. Research conducted concluded that the dual role of street sweeper women as single parents in the family in the city of Pekanbaru, besides working as street sweepers, most of them were mothers, who had the responsibility to educate children, take care of family matters, and also act as family breadwinner. In addition to working as a street sweeper, it turns out that some of them work side-by-side, such as becoming a household assistant in a neighbor's home in the neighborhood. It is known that the motivating factors of women who work as street sweepers are not only motivated by the economic factors of the poor families but are influenced by a strong desire to keep working, and for a variety of reasons, such as being influenced by social interaction that grows in the street sweeper environment. Keywords: Dual Role, Working Women, Role Conflict